Oligonucleotides Incorporating Palladacyclic Nucleobase Surrogates - Maity SK; Lonnberg T (WILEY-V C H VERLAG GMBH, 2022)
An oligonucleotide incorporating a palladacyclic nucleobase has been prepared by ligand-directed metalation of a phenylpyridine moiety. This oligonucleotide hybridized with natural counterparts placing any of the canonical nucleobases opposite to the palladacyclic residue. The palladated duplexes had B-type conformation and melting temperatures comparable to those of respective unmodified duplexes with a single mismatch. In the duplexes placing C, G or T (but not A) opposite to the palladacyclic residue, greatly increased absorptivity suggested formation of a Pd-II-mediated base pair. Absorptivity and ellipticity of these duplexes persisted even at the highest temperatures applicable in T-m and CD experiments (90 degrees C). Evidently the Pd-II-mediated base pairs do not dissociate under the experimental conditions.